The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3122/jabfm.2011.04.100296
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Timely and Available Prenatal Studies by Electronic Health Records

Abstract: Background:The government is encouraging the adoption of electronic medical records (EMRs). There is little information about using EMRs in the obstetric literature and none about using them in family medicine residencies. Our purpose was to assess if using an EMR was associated with improvement in the ordering and availability of prenatal tests.Methods: A retrospective chart review comparing the rate at which prenatal laboratory values were present on the chart, ordered on time, and recorded on a prenatal flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In an urban residents’ clinic, adopting an EMR was associated with an improved rate at which prenatal tests were ordered on time, present on the chart, and recorded on a prenatal flow sheet. (27) EMR adoption may improve documentation without adversely affecting workflow. (28, 29) Even within an existing EMR, improved electronic supports may increase measures of quality care.…”
Section: Discussionmentioning
confidence: 99%
“…In an urban residents’ clinic, adopting an EMR was associated with an improved rate at which prenatal tests were ordered on time, present on the chart, and recorded on a prenatal flow sheet. (27) EMR adoption may improve documentation without adversely affecting workflow. (28, 29) Even within an existing EMR, improved electronic supports may increase measures of quality care.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Because obstetric care can span a variety of outpatient and inpatient settings, communication between different medical providers is of prime importance. 2,8 To translate these trends into discernible clinical outcomes, this study investigates the outcomes of improved transmission of prenatal test results, specifically maternal hepatitis B and human immunodeficiency virus (HIV) serology, between the outpatient and inpatient obstetric setting after implementation of an electronic prenatal record system. [4][5][6][7][8] Two previous studies have demonstrated increased availability and communication of prenatal records in the obstetric setting after implementation of an electronic medical record.…”
Section: Level Of Evidence: IIImentioning
confidence: 99%
“…Fortunately, the unprecedented spread of mobile technology has made it possible to develop mHealth platforms that can be used to provide similar services to hard-to-reach communities in resource-limited settings [23,27]. This has led to improved quality of care and decreased rate of unnecessary testing, and has allowed for early institution of evidence-based interventions that improve birth outcome [28-31]. …”
Section: Introductionmentioning
confidence: 99%